2015
DOI: 10.14198/jhse.2015.101.08
|View full text |Cite
|
Sign up to set email alerts
|

Management of metabolic resources for a 20-km cycling time-trial using different types of pacing

Abstract: Chuckravanen, D., & Rajbhandari, S. (2015). Management of metabolic resources for a 20-km cycling timetrial using different types of pacing. J. Hum. Sport Exerc., 10(1), pp.95-103. Pacing is crucial for improving human performance in time-trial physical exercise. This study examined the effect of different types of pacing (self pace, variable pace and even pace) on the energy expended from the aerobic system and anaerobic system for a 20-km time-trial cycling exercise. In addition, the degree of homeostatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Considering the potential to improve pacing behavior [30], evidence is needed so coaches and athletes may develop optimal pacing strategies for training and competition. A comparison of three pacing strategies (i. e. self-pace, variable and even pace) in cycling demonstrated that even pacing is relatively more dependent on the aerobic energy system, whereas variable pacing is more dependent on the anaerobic energy system [8]. Thus, adopting a pacing strategy may impact directly on the metabolic demands of endurance training and competition.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the potential to improve pacing behavior [30], evidence is needed so coaches and athletes may develop optimal pacing strategies for training and competition. A comparison of three pacing strategies (i. e. self-pace, variable and even pace) in cycling demonstrated that even pacing is relatively more dependent on the aerobic energy system, whereas variable pacing is more dependent on the anaerobic energy system [8]. Thus, adopting a pacing strategy may impact directly on the metabolic demands of endurance training and competition.…”
Section: Introductionmentioning
confidence: 99%